Identification of biomarkers associated with exhausted CD8 + T cells in the tumor microenvironment of intrahepatic cholangiocarcinoma based on Mendelian randomization and bioinformatics analysis - LiuXing Feng; Quan Yuan; Hao Yu; RongJie Ye; ZhenHao Xie; JiaHuan Xu; XiuDong Li; ShuangJia Wang (Discover Oncology)
Abstract Intrahepatic cholangiocarcinoma (iCCA) represents a growing health concern due to its increasing incidence and poor prognosis, highlighting the urgent need for biomarkers and therapeutic targets. This study utilized BayesPrism deconvolution, Weighted Gene Co-expression Network Analysis (WGCNA), and Summary Mendelian Randomization (SMR), integrated with single-cell RNA sequencing (scRNA-seq) data, to analyze the tumor microenvironment. Seven distinct cell subpopulations, including Exhausted CD8 + T cells (Tex), were identified. Notably, scPagwas analysis revealed gene enrichment in UQCRH, HINT1, and AKR1C3, associated with Tex. BayesPrism analysis confirmed their increased presence in the tumor microenvironment, indicating a role in immune evasion. WGCNA identified 594 genes linked to these cells, with PNO1 and AKR1C5P emerging as potential disease-associated genes. These findings highlight the critical role of Tex in immune suppression and identify key genes for further investigation in iCCA progression and treatment strategies.